Sea-ice thermodynamics can determine waterbelt scenarios for Snowball Earth - J. Hörner; A. Voigt (Earth System Dynamics, 2024)
Snowball Earth refers to multiple periods in the Neoproterozoic during which geological evidence indicates that the Earth was largely covered in ice. A Snowball Earth results from a runaway ice–albedo feedback, but there is an ongoing debate about how the feedback stopped: with fully ice-covered oceans or with a narrow strip of open water around the Equator. The latter states are called waterbelt states and are an attractive explanation for Snowball Earth events because they provide a refugium for the survival of photosynthetic aquatic life, while still explaining Neoproterozoic geology. Waterbelt states can be stabilized by bare sea ice in the subtropical desert regions, which lowers the surface albedo and stops the runaway ice–albedo feedback. However, the choice of sea-ice model in climate simulations significantly impacts snow cover on ice and, consequently, surface albedo.